A numerical study on the enhanced drag reduction and wake regime control of a square cylinder using dual splitter plates. (15th March 2020) - Dash, Sunil Manohar; Triantafyllou, Michael S; Alvarado, Pablo Valdivia Y
Highlights: A dual splitter plate flow control device for a square cylinder is introduced. Fluctuating drag, lift forces and aerodynamic moments are characterized. Wake regime as functions of the splitter plate(s) length and their gap is reported. Optimum splitter plate(s) length and their gap for lowest drag is determined. Benefits of dual splitter plates over long single splitter plate is discussed. Abstract: In this paper, a dual splitter plate flow separation control device is introduced for a low Reynolds number flow ( Re = 100) around the square cylinder of length L to achieve higher drag reduction and improved wake regime control compared to the conventional single splitter plate control devices. Here, two splitter plates of the same length W (ranging from 0.25 L to 2.50 L) are symmetrically attached on the rear surface along the horizontal centerline of the square cylinder with a spacing H (ranging from 0.0 L to 1.0 L) between them. The numerical study is performed using the in-house developed flexible forcing immersed boundary-lattice Boltzmann solver [1] to investigate the effects of dual splitter plate on the flow regime and flow-induced forces. The shear layer interaction with the splitter plates, as well as the vorticity and pressure distribution in the near wake region, are significantly modified by varying W and H, and four different flow regimes (Type I to Type IV) are identified from the observations. Among these flow types, the Type III flow pattern displays an accelerating flow in the wake region that is found to be most beneficial for higher base pressure recovery and drag reduction. Furthermore, dual splitter plates suppress von-Karman vortex shedding and lift force fluctuation, and produce higher drag reduction (≈ 21%) at less than half of the plate length of a single splitter plate. It is also noticed that a dual splitter plate configuration seems to be an optimum arrangement, since adding more splitter plates (up to 5 numbers were tested) on the rear surface of the square cylinder does not change the wake characteristics nor shows any improvements in the drag reduction.